2017
DOI: 10.1186/s40885-017-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery intima-media thickness and hypertensive heart disease: a short review

Abstract: Sustained by its relative ease of assessment, carotid artery intima-media thickness (cIMT) has emerged as an important surrogate marker of target organ damage in hypertensive heart disease over the last three decades. However, the prognostic utility of cIMT in hypertensive heart disease differs depending on its application. This review outlines cIMT and its prognostic utility among patients with hypertensive heart disease. It provides an overview of limitations of cIMT and areas for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
1
16
0
2
Order By: Relevance
“…Baldassarre et al showed on sample of 4,482 patients that CIMT was associated with increased cardiovascular risk [22], which was also confirmed by Kokubo et al in a study on 4,724 patients [24]. Utility of CIMT can predict vascular incident in asymptomatic patients [25]. In PE, the placental helix arteries fail to lose their musculoelastic layers, leading exclusively to decreased placental perfusion [26].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Baldassarre et al showed on sample of 4,482 patients that CIMT was associated with increased cardiovascular risk [22], which was also confirmed by Kokubo et al in a study on 4,724 patients [24]. Utility of CIMT can predict vascular incident in asymptomatic patients [25]. In PE, the placental helix arteries fail to lose their musculoelastic layers, leading exclusively to decreased placental perfusion [26].…”
Section: Discussionmentioning
confidence: 82%
“…Increased CIMT is an independent predictor of stroke and cardiovascular events [20][21][22][23][24][25]. Eikendal et al have concluded in 3,067 adult patients younger than 45 years of age without symptomatic cardiovascular disease that CIMT may be a marker for cardiovascular risk [20].…”
Section: Discussionmentioning
confidence: 99%
“…34 The intima-media thickness is also increased in hypercholesterolaemic patients compared to controls, 35 and has become a convenient marker for atherosclerosis. 36 Oxidation of LDL cholesterol is key in the initiation of atherosclerosis 7 and may also trigger vascular remodelling by enhancing smooth muscle cell proliferation and collagen deposition, leading to increased intima-media thickness. Increased deposition of elastic and collagen fibres was observed in the present study, shown by VVG-stained sections of aortic arch and thoracic aorta, suggesting increased atherogenesis, as shown previously.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular remodeling (VR) persists throughout the course of hypertension and is characterized by chronic, continuous, and complex changes in vascular structure and abnormalities in vascular functions (Hayashiet al , 2009;Lemarie et al , 2010;Zhang et al , 2019). VR, as an important indicator of the progression of hypertension, is closely related to the severity and prognosis of the disease (Mulvany, 2012;Magnussen, 2017;Brown et al , 2018). Angiotensin II (AngII)-induced dysfunction of vascular smooth muscle cells (VSMCs) plays a critical role in hypertensive VR (Das et al , 2018), but the potential molecular mechanisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%